Evaluation and Delineation of Sulfur Groundwater Leakages Using Electrical Resistivity Techniques in Hit Area, Western Iraq - Mohammed, Osama J.; Abed, Ali M.; Alnuaimi, Mohammed A. (Iraqi Journal of Science, 2021)
Electrical resistivity methods are one of the powerful methods for the detection and evaluation of shallower geophysical properties. This method was carried out at Hit area, western Iraq, in two stages; the first stage involved the use of 1Dimensional Vertical Electrical Sounding (VES) technique in three stations using Schlumberger array with maximum current electrodes of 50m. The second stage included the employment of two dimension (2D) resistivity imaging technique using dipole-dipole array with a-spacing of 4m and n-factor of 6 in two stations. The 1D survey showed good results in delineating contaminated and clear zones that have high resistivity contrast. Near the main contaminated spring, the 2D resistivity imaging technique was applied in four sections length (100 m) using a dipole-dipole array position coincided with the three points VES. We compared the results of the interpretation of imaging the techniques 2D and VES. We found that the 2D imaging resistivity technique was better than VES survey in determining the distribution of pollution under the surface in the area surveyed. It was also found that the polluted water is located about 5 m below the surface. The largest amount of leakage was found towards the northeast and coincided with the direction of the groundwater movement. Spring water has leaked from outside the region through the Kubaisah area. Most of this water is contained in quaternary deposits and karst gypsum fractures.